Monitoring of reconstruction of rigid airfield pavements - Агєєва, Г. М.; Крівельов, Л. І. (Proceedings of National Aviation University (archive), 1998)
A plan to carry out a set of both theoretical and experimental tests providing scientific accompaniment for designing and engineering processes is developed. It was determined a period for pavement strength quantative indexes with due regard for real conditions of civil engineering and operation. It was studied a character of functioning of multicourse pavement defined through ratio of constructive layers rigidity values. Defined is smaller rated theoretical values for classification number of PCN pavement as compared to supposed design value